Iowa RBA, September 27-October 2, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Six emails of Iowa RBA updates for September 27 to October 2, 1999. Highlights of the updates include sightings of a Brown Pelican, an Ibis species, and a Black-throated Blue Warbler. Epson - sheet feed/flatbed